Soldiers and Scholars: Ritual Dilemmas among National Religious Combat Soldiers in the Israel Defense Forces. (June 2020) - Stern, Nehemia; Ben-Shalom, Uzi
This article explores how the practice of Jewish rabbinic law within the combat ranks of the Israel Defense Forces can be used as an ethnographic medium through which anthropologists may better contextualize the social and political tensions that characterize Jewish religious nationalism in Israel. We argue that national religious combat soldiers rarely turn to rabbinic legal tracts, or to the overlapping levels of military and civilian rabbinic leadership in their immediate efforts to resolve the everyday ritual dilemmas of their service. Rather, these dilemmas are primarily addressed and (always imperfectly) resolved on the small-scale intra-unit level. Through this ethnographic window into the religious and ritual aspects of military life, this article ultimately argues that the experience of political piety in Israel (and perhaps the wider Middle East) hinges not so much upon the power play between opposing religious and secular institutions but rather in the daily ambivalences and ambiguities experienced by individual adherents as they go about their daily lives.